2021
DOI: 10.1167/iovs.62.3.18
|View full text |Cite
|
Sign up to set email alerts
|

A Porcine Organ-Culture Glaucoma Model Mimicking Trabecular Meshwork Damage Using Oxidative Stress

Abstract: Re-cellularization of the trabecular meshwork (TM) using stem cells is a potential novel treatment for ocular hypertension associated with glaucoma. To assess the therapeutic efficacy of this approach, improved in vivo and ex vivo models of TM pathophysiology are needed. Here, we investigate whether oxidative stress, induced by hydrogen peroxide (H 2 O 2), can model glaucomatous ocular hypertension in the readily available porcine anterior segment organ culture model. METHODS. The impact of H 2 O 2 on TM cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Other mechanistic aspects such as the potential involvement of released substances/proteins (e.g., MMPs) can also be ascertained by sampling the effluent from these perfused segments. Such data has been reported using partially intact ex-vivo ANC eye segments of numerous different species (Llobet et al, 1999;Crosson et al, 2005;Webb et al, 2006;Keller et al, 2017;Mao et al, 2012;Boussommier-Calleja et al, 2012;Ren et al, 2016;Snider et al, 2021), and also using a whole perfused eye models (Shahidulla et al, 2005;Zhou et al, 2017). Figure 16B depicts example data obtained for two IOP-lowering agents, cabergoline and FR-190997, which enhanced outflow of perfused media in a time-dependent manner from such ex-vivo models.…”
Section: Ex-vivo Screening Models To Evaluate Potential Intraocular Pressure-lowering Agentssupporting
confidence: 57%
“…Other mechanistic aspects such as the potential involvement of released substances/proteins (e.g., MMPs) can also be ascertained by sampling the effluent from these perfused segments. Such data has been reported using partially intact ex-vivo ANC eye segments of numerous different species (Llobet et al, 1999;Crosson et al, 2005;Webb et al, 2006;Keller et al, 2017;Mao et al, 2012;Boussommier-Calleja et al, 2012;Ren et al, 2016;Snider et al, 2021), and also using a whole perfused eye models (Shahidulla et al, 2005;Zhou et al, 2017). Figure 16B depicts example data obtained for two IOP-lowering agents, cabergoline and FR-190997, which enhanced outflow of perfused media in a time-dependent manner from such ex-vivo models.…”
Section: Ex-vivo Screening Models To Evaluate Potential Intraocular Pressure-lowering Agentssupporting
confidence: 57%
“…Increasing MMP activity causes an elevated AH outflow rate, whereas inhibiting MMP activity decreases the AH outflow rate [ 71 ]. A recent study using a porcine model showed similar results, indicating that reduced MMP-2 and -9 activity is related to elevated IOP [ 72 ]. ECM composition changes can be observed when the AH outflow rate is pushed from equilibrium [ 73 ].…”
Section: Resultsmentioning
confidence: 58%
“…Increased matrix metalloproteinase (MMP) activity in the trabecular meshwork elevates AH outflow, which in turn reduces intraocular pressure (IOP). However, decreased MMP activity in the trabecular meshwork decreases AH outflow, which causes elevated IOP [ 63 , 65 , 71 , 72 , 73 ].…”
Section: Figurementioning
confidence: 99%
“…In this study, we utilized a hydrogen peroxide (H 2 O 2 ) model to mimic glaucomatous ocular hypertension in vitro. H 2 O 2 induces acute oxidative stress to TM which leads to the pathogenesis of POAG [ 68 ], this model was proved to be a useful platform which resulted in TM cellular dysfunction without the destruction of the TM structure [ 69 ], which made this model suitable for the hypothesis that gut microbiota dysbiosis regulates TM cellularity through innate immune response.…”
Section: Discussionmentioning
confidence: 99%